INVESTIGATING PRIMARY SCHOOL STUDENTS’ GRAMMATICAL ERRORS IN WRITING: DULAY’S SURFACE STRATEGY TAXONOMY - Wensi Alka; Dzulfikri Dzulfikri; Khaula Amelia Khusna (Journal of English Educational Study (JEES), 2023)
This study was carried out to identify different types of grammatical errors made by primary school students since some previous studies only conducted the same research with high school students as the participants. This study used a descriptive qualitative research design. The participants were 40 fourth-grade students from SD Muslim Cendekia Batu. Students' writing products were used as the instrument. The data were analyzed, identified and classified based on Dulay's (1982) surface strategy taxonomy. The data show that the students made 79 grammatical errors, with errors of omission accounting for 25 items (31.6%), 21 (26.5%) errors  in addition, 26 errors (32.7%) in misformation, and 7 (9.2%) errors in misordering. The findings reveal that students lack grammar mastery; therefore, they frequently create their own rules in writing a text. To summarize, the student's understanding of the use of English structure remained low. The researcher's recommendations for future researchers are to focus more on the sources of the students' errors and to identify and determine the appropriate strategies to overcome students’ grammatical errors.